Nicaea, American Populism, and Christian Nationalism: Lessons from the Field - Trice, Michael Reid (The ecumenical review, 2024)
On the 1700th anniversary of the First Ecumenical Council of Nicaea, this article reviews the history and leadership of the council by pursuing the following question: What does Nicaea teach us about best practices in adaptive leadership from the Christian past to help us address rising authoritarianism today? The article examines the November 2024 US presidential election as demonstrative of rising popular authoritarianism in the United States, acknowledging how an America First doctrine is reshaping the political and religious landscapes. The article purports that lessons from the field in the first centuries of Christianity, to Nicaea, can guide us today and tomorrow. The article also aims to be a resource that will assist leaders as they work tirelessly in a polarizing national landscape.